THE YEMENI ARCHITECTURE INFLUENCED THE CULTURE IN THE TOWER HOUSE IN BAB AL YEMEN, SANA’A - Abu Bakar Abd Hamid; Muhammad Danial Ismail; Reem Abdullah Hames Al-Awjari, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
This paper study on the traditional tower house in Old City Sana’a as known as Bab al Yemen. It focusing how the local context with lifestyle and culture determine the traditional architecture and design in Bab al Yemen and different regions of Yemen and Arab regions, according to nature, climatic conditions, culture, traditional values, and native knowledge. Overview for architecture and design during the twentieth century, civilisation and the Islam perspective in the Arab region, and selected the traditional tower house in Yemen as a case study. In addition to the analysis the traditional tower house form and layout in Sana’a city, the design and elements of the house; spatial organization, construction systems and building materials, and window openings included ornaments patterns. The study summarises the aspects of lifestyle and culture in the traditional house as an ancient traditional knowledge for character of architecture and design. In conclusion, the traditional tower house in Bab al Yemen, designed according to the local context and indigenous traditional knowledge, have influenced traditional tower house architecture; the house elements and design satisfies the lifestyle and culture aspects. This includes design aspects related to the house layout, the application of traditional design, the traditional building material, the Islamic values in house design, the exterior appearance of the house and lifestyle aspect. heritage and indigenous traditional knowledge toward sustainable architecture.